Longman preparation series for the TOEIC test - Lougheed, Lin (Longman, 1996)
Ideal for a TOEIC "RM" Preparation Course or self-study, the Longman Preparation Series for the TOEIC "RM" Test presents the strategies, skills, and practice to give students the confidence needed to increase their scores on the Test of English for International Communication (TOEIC "RM"). Introductory TOEIC "RM" and the Advanced TOEIC "RM" Test Courses provide step-by-step strategies, skills, and practice for each section of the TOEIC "RM" Test. Practice content is consistent with the general business situations typical in the test. Each level includes practice tests and answer keys with explanatory information